2013
DOI: 10.1177/1757913912470052
|View full text |Cite
|
Sign up to set email alerts
|

A literature-based intervention for older people living with dementia

Abstract: In light of quantifiable data of limited but indicative status, together with strongly corroborative qualitative evidence, engagement in reading-group activity appeared to produce a significant reduction in dementia symptom severity. Staff interviews indicated the contribution of reading groups to well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 16 publications
2
71
0
Order By: Relevance
“…The current findings, combined with existing qualitative (Billington et al, 2013;CRILS, 2014) and quantitative (Billington et al, 2013) This evaluation does not permit definite conclusions about SR's mechanisms of impact, although it is possible to speculate on the basis of existing literature. Social contact, for example, is known to be an important requirement for dementia patients (van der Roest et al, 2007), and SR provides a supportive forum in which residents can engage in meaningful interactions with facilitators, healthcare staff, and one another.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The current findings, combined with existing qualitative (Billington et al, 2013;CRILS, 2014) and quantitative (Billington et al, 2013) This evaluation does not permit definite conclusions about SR's mechanisms of impact, although it is possible to speculate on the basis of existing literature. Social contact, for example, is known to be an important requirement for dementia patients (van der Roest et al, 2007), and SR provides a supportive forum in which residents can engage in meaningful interactions with facilitators, healthcare staff, and one another.…”
Section: Discussionmentioning
confidence: 64%
“…Whilst the conclusions that can be drawn from the current data are limited, our findings are consistent with an existing evidence base that demonstrates the valuable contribution of nonpharmacological interventions, specifically participatory artsbased strategies, for the care of dementia patients (Gerdner, 2000). Although further research is needed, existing work demonstrates that SR is associated with a reduction in neuropsychiatric symptoms (Billington et al, 2013); is able to utilise emotionally powerful literature to trigger 'awakenings' in people living with dementia; offer a richly attentive presentness in the activity and a sense of activated newness or renewal in the experience (which is different from mindfulness or reminiscence therapy); offer supportive social contact; and provide enjoyment, meaningfulness, and an enhancement of listening, memory and attention (Billington et al, 2013;CRILS, 2014). Correspondingly, the current results indicate that three months of reading group participation has a quantifiable impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, as the author states, such environments are no substitute for well-trained empathizing staff, however they can be used to therapeutic advantage. As can group reading activities, which are the focus of the paper by Billington et al 3 Here it was found that engagement in a literature based intervention could produce a significant reduction in dementia symptom severity, although it was recognized that further research is required.…”
mentioning
confidence: 99%